Research note: Understanding Post-COVID Travel Intentions: The Role of Motivations, Anxiety, Health Consciousness, and Resilience - Dila MAGHRIFANI; Wulan PERMATASAR (Tourism and Hospitality Management)
Purpose – This study aims to provide empirical evidences on how post-pandemic travel intentions are formed in relation to the influences of travel motivations and pandemic-related factors (i.e., pandemic anxiety, health consciousness, and pandemic resilience). Also, this study aims to understand the differences in this travel intentions’ formation between potential and repeat visitors. Methodology/Design/Approach – An online survey was distributed to Indonesian potential and repeat visitors travelling to Australia, collecting 500 valid questionnaires. The factor analysis and hierarchical multiple regression were used to understand the influences of travel motivations, pandemic anxiety, health consciousness, and pandemic resilience in determining potential and repeat visitors’ travel intentions. Findings – The findings indicated that pandemic anxiety, health consciousness, and pandemic resilience jointly influenced the motivation-intention relationships for both potential and repeat visitors. Potential visitors’ travel intentions were primarily driven by pandemic resilience, whereas repeat visitors’ intentions were significantly influenced by novelty seeking, social seeking motivations, and health consciousness. Originality of the research – By developing and testing a model that integrates travel motivations and pandemic-related factors in determining potential and repeat visitors’ travel intentions, this offers valuable insights for destination marketers, aiding in the sector’s recovery during and following challenging times.